PENGEMBANGAN MEDIA FLASHCARD UNTUK MENINGKATKAN SIKAP TOLERANSI MATA PELAJARAN PPKN SISWA KELAS 2 DI SDN MEKAR MUKTI 01 - Aisyah, Siti (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This research and development was carried out to determine the attitude of tolerance in grade 2 elementary school students in PPKn learning, on theme 7 regarding the diversity of individual characteristics, especially in religious and ethnic cultural diversity. This research is a combination of qualitative data and quantitative data (Research and Development). This research was conducted on class II students in elementary schools. This research and development produced a flashcard media product for class 2 Civics learning at SDN Mekar Mukti 01. The results of the research using the N-Gain Score calculation, obtained a value of 0.57 with the criteria of